PROFIL HEDONIK KEMPLANG PANGGANG KHAS PALEMBANG - Ikromatun Nafsiyah; Seftylia Diachanty; Selly Ratna Sar; Guttifera; Rani Ria Rizki; Siti Lestari; Nanda Syukerti (Clarias : Jurnal Perikanan Air Tawar, 2022)
Palembang's kemplang panggang is one of Palembang's original foods that is populer both inside and outside of Palembang. Kemplang is widely sold and produced in Palembang. The number of baked kemplang products makes consumers confused in choosing baked kemplang products which later became the basis for this research. This study was purposed to determine the level of consumer/panelist preference for baked kemplang sold in markets around Palembang. Kemplang Panggang Palembang of this study was purchased from three different markets and different trade names. This study was divided into two stages, namely the preparation stage and the implementation stage of hedonic testing carried out by 25 semi-trained panelists with four parameters such as aroma, color, taste, and texture. The highest results on the parameters of aroma, color, taste, and texture were found in the sample with code 303 with a “like” level. Based on these results, it can be concluded that sample 303 is the most preferred baked kemplang compared to other baked kemplang samples